Graduação citológica de mastocitomas caninos: correlação com graduação histológica e sobrevida - Modesto, Talita Cristina (2022)
Mast cell tumor is one of the most commonly diagnosed neoplasia in dogs, and it shows a variable biological behavior. The diagnostic is made using cytopathology and/or histopathology. The histological grading is considered the gold standard test to predict the prognosis of mast cell tumor. However, studies have been made using the cytological classification to provide similar information in a faster, less invasive and more accessible way. Therefore, this paper aims raise epidemiological data, perform cytological graduation, and correlate it with the histological grading and survival time of dogs diagnosed with cutaneous mast cell tumor at the Veterinary Hospital of Uberlândia Federal University, in the years of 2016 to 2021. For that, 83 cytological and histological slides from 72 animals were reevaluated and graduated by pathologists. The agreement between the grading systems were made using kappa statistics test, the survival time was analyzed with Kaplan-Meier test, and the univariate Cox regression analysis was used to compare the predictor variables of the cytological and histological grades for the canine mast cell tumor and the global survival time. In all analysis the significant level was of p≤0.05. The cytology classification when compared to the 2-tier histologic grading, high grade and low grade, had a moderated agreement (kappa 0.566), and the cytological grading predicted correctly the histologic grade in 84.3% of the cases. When evaluated the correlation between the survival time and the cytological grade, there was a higher death rate in the group with high grade mast cell tumor compared to the low grade, pointing a correlation between the survival time and the cytological grade (p= 0.009). Despite that, the cytological grade compared to the 3-tier histological grade, grade I, grade II and grade III, had a poor agreement. This research concludes that the cytological grade is useful to help the treatment planning and to provide prognostic information that precedes the tumor removal, showing a good correlation with the 2-tier histologic grading and with the survival time of the animals.